Boosting Students’ Speaking Skills Through the Chain Story Game - Kholid, Mohammad Fikri Nugraha; Rini, Yulan Puspita; Yulia, Jhija (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
Mastering speaking skills is essential for effective communication in English language learning. However, many students face challenges in developing these skills. Preliminary research at SMA N 1 Baradatu revealed that 60% of tenth-grade students scored below the minimum competency criterion (KKM) of 72. This study aimed to examine the impact of using the chain story game on the speaking ability of tenth-grade students at SMA N 1 Baradatu during the 2024/2025 academic year. A quantitative approach with a quasi-experimental design was employed. The population comprised tenth-grade students at SMA N 1 Baradatu, with a sample of 68 students: 34 from class X IPA 2 and 34 from class X IPS 1. Data collection involved providing treatment to the experimental group, while the control group received no intervention. Oral pre-tests and post-tests were conducted for both groups, and the data were analyzed using SPSS Statistics 25. Since the data were neither normally distributed nor homogeneous, the Mann-Whitney U test was used. The analysis revealed a significance value (p-value) of 0.000, lower than α = 0.05, leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (Ha). The results demonstrate that the chain story game significantly improved students' speaking abilities. This study highlights the potential of interactive and innovative techniques, such as the chain story game, to address challenges in speaking skill development and enhance student engagement in English language learning.